1H, 15N and 13C chemical shift assignments of the BA42 protein of the psychrophilic bacteria Bizionia argentinensis sp. nov - Smal, Clara; Aran, Martin; Lanzarotti, Esteban Omar; Papouchado, Mariana; Foti, Marcelo; Marti, Marcelo Adrian; Coria, Silvia Herminda; Vázquez, Susana Claudia; Bercovich, Andrés; Mac Cormack, Walter Patricio; Turjanski, Adrian; Gallo, Mariana; et al. (Biomolecular NMR Assignments)
BA42 is a protein belonging to the psychrophilic bacteria Bizionia argentinensis sp. nov. Bioinformatics analysis showed that it presents significant sequence identity with a Pfam A family, DUF 477, found both in eukarya and eubacteria but of unknown function in all these organisms. Here, we report the NMR spectra assignment of this 145 amino acid protein. These data will allow performing NMR structural studies with the aim of using the three-dimensional structure as relevant information in order to determine the function of this family of proteins. Fil: Smal, Clara. Fundación Instituto Leloir; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Aran, Martin. Fundación Instituto Leloir; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Lanzarotti, Esteban Omar. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química, Física de los Materiales, Medioambiente y Energía. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química, Física de los Materiales, Medioambiente y Energía; Argentina Fil: Papouchado, Mariana. Biosidus S. A.; Argentina Fil: Foti, Marcelo. Biosidus S. A.; Argentina Fil: Marti, Marcelo Adrian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química, Física de los Materiales, Medioambiente y Energía. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química, Física de los Materiales, Medioambiente y Energía; Argentina Fil: Coria, Silvia Herminda. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Vázquez, Susana Claudia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Bercovich, Andrés. Biosidus S. A.; Argentina Fil: Mac Cormack, Walter Patricio. Ministerio ...